Efektivitas Expressive Writing Therapy dalam Menurunkan Kecemasan Santri yang Mengalami Broken Home - Zahrotul Jannah (Jurnal Psikologi Islam dan Budaya, 2022)
This study aims to determine the effectiveness of expressive writing therapy in reducing the level of anxiety experienced by broken home students at one of the Islamic boarding schools in Sumenep. The research method used true experiment pretest-posttest control group design with five subjects in each group (control and experiment). Data collection used the HARS (Hamilton Anxiety Rating Scale). The results showed that expressive writing therapy was effective in reducing the level of anxiety experienced by broken home students at the Annuqayah Islamic Boarding School (PPA) Lubangsa Selatan Putri.